Navigating Character Education: The Multifaceted Role of Social Studies Teachers and Socio-Cultural Barriers in Elementary Schools - Melina Maula (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
The role of a Social Studies (IPS) teacher extends far beyond mere knowledge transfer; it encompasses the critical responsibility of shaping students' social character and civic competence. This study aims to determine the multifaceted roles of teachers in enhancing IPS learning and to identify the supporting and inhibiting factors in character formation at SDN 03 Patilanggio. Employing a qualitative descriptive method, data were systematically collected through direct observation, in-depth interviews with teachers and the school principal, and documentation study. The data were analyzed using an interactive model comprising data reduction, display, and conclusion drawing. The results reveal that teachers perform four primary roles: as educators planning the curriculum, as demonstrators executing active learning, as role models exhibiting positive social behavior, and as coaches instilling discipline. While these roles are supported by teachers' professional competence and clear school visions, a significant inhibiting factor was identified. Teachers frequently encounter socio-cultural barriers, specifically miscommunication and resistance from parents and school foundations regarding the firmness required in character building. In conclusion, optimizing IPS learning requires not only pedagogical mastery from the teacher but also a highly synergistic and transparent partnership between the school, parents, and the community to ensure consistent character education.